Dangerous Behavior and Intractable Axial Skeletal Pain in Performance Horses: A Possible Role for Ganglioneuritis (14 Cases; 2014–2019) - Story, Melinda R.; Nout-Lomas, Yvette S.; Aboellail, Tawfik A.; Selberg, Kurt T.; Barrett, Myra F.; Mcllwraith, C. Wayne; Haussler, Kevin K. (Frontiers in Veterinary Science, 2021)
Introduction: Dangerous behavior is considered an undesired trait, often attributed to poor training or bad-tempered horses. Unfortunately, horses with progressive signs of dangerous behavior are often euthanized due to concerns for rider safety and limitations in performance. However, this dangerous behavior may actually originate from chronic axial skeleton pain. This case series describes the medical histories and clinical presentations of horses presented for performance limitations and dangerous behavior judged to be related to intractable axial skeleton pain. Material and Methods: 14 horses that developed severe performance limitations resulting in euthanasia were included. A complete spinal examination and behavioral responses, gait and neurologic evaluations, diagnostic imaging, gross pathologic and histopathologic examinations of the axial skeleton were performed on all horses. A tentative diagnosis of the affected spinal region was formulated using medical records, owner and trainer complaints, and antemortem examination findings. The selected spinal regions were further examined with gross and histopathologic evaluations of the associated osseous, soft tissue and neural tissues. Results: Ten horses showed severe behavioral responses during the myofascial and mobilization examinations. Based on an aggregate evaluation, the cervicothoracic and lumbosacral regions were the most common regions believed to be the primary area of concern. All horses had moderate to severe ganglionitis present at multiple vertebral levels. Subdural and epidural hemorrhage or hematomas were a common finding (71%) in the cervicothoracic and lumbosacral regions. Discussion: In this case series, neuropathic (i.e., structural) pain was judged to be the underlying cause of dangerous behavior. The dorsal root ganglia (DRG) serve an important role in relaying peripheral sensory information to the central nervous system and ganglionitis has been associated with neuropathic pain syndromes. This series highlights the need for more in-depth understanding of pain behavior and its clinical presentation and progression in chronic or severely affected horses. Limitations of the study are the lack of age-matched control DRG and the incomplete collection of DRG from every vertebral level of interest.